A COMPARATIVE ANALYSIS OF DEFINITIONS OF ADVERTISING - Dilnoza Rasulovna Sobirova (International Journal of Literature and Language Studies, 2026)
This article discusses advertising and the definitions attributed to it. It provides an analysis of various definitions of advertising and presents the author's perspective on them.